Investigating barriers to green human resource management implementation at a South African government department - Farai Nyika; Precious Nompumelelo Nqobile Nkosi-Mahla; Khalida Akbar (Менеджмент та підприємництво: тренди розвитку)
The purpose of this study is to identify the barriers faced by Department X, a government body in Gauteng, South Africa, when trying to apply Green Human Resource Management (GHRM) principles. To help businesses become more sustainable and accelerate the transition to a green economy, GHRM combines environmental management with HR initiatives. Design/methodology/approach: With Institutional Theory and the Resource-Based View guiding the study, eight HR experts participated in semi-structured interviews as part of a qualitative approach. These experts were selected from a population of 650 employees through purposeful sampling, which was employed to identify the participants who were most pertinent to the research objectives. Purposeful sampling guarantees that participants have firsthand knowledge or participation in GHRM practices within Department X. Findings: The study finds barriers that include resistance to change, a lack of commitment from leadership, limited resources, and regulatory hurdles. The department's ability to align HR practices with sustainability objectives is hindered by these challenges, which in turn harms environmental efforts. Practical implications: The findings highlight the critical role of effective leadership, efficient distribution of resources, and adherence to regulations in fostering GHRM, increasing resistance to climate change, and enabling development programs targeted towards young people and lead to greater efficiency in the South African public service. Originality/value: This study adds to the existing body of knowledge by highlighting the public sector-specific challenges to GHRM implementation in a developing nation setting, with a focus on the interplay between organisational and institutional dynamics.